2014
DOI: 10.1002/adma.201400515
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance in Non‐Toxic Earth‐Abundant Copper Sulfide

Abstract: A new type of high performance thermoelectric material Cu2‐xS composed of non‐toxic and earth‐abundant elements Cu and S is reported. Cu2‐xS surprisingly has lower thermal conductivity and more strikingly reduced specific heat compared to the heavier Cu2Se, leading to an increased zT to 1.7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
608
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 678 publications
(667 citation statements)
references
References 34 publications
31
608
0
6
Order By: Relevance
“…The electron diffraction pattern obtained from the H-i phase is purely hexagonal, with no superlattice--reflecting the absence of a structural modulation in this phase. Previous resistivity studies at various levels of nonstoichiometry in Cu 2−x S showed that the phase transition is abrupt on heating and cooling only when the Cu vacancies (x) present are less than 1% of the atomic weight (15), thus confirming the stoichiometry of our nanoparticles. Since Cu vacancies are acceptors in Cu 2 S, the hole carrier (hereafter denominated as "e + ") concentration in our p-type nanoplates n e + is less than 1%.…”
Section: Resultssupporting
confidence: 56%
“…The electron diffraction pattern obtained from the H-i phase is purely hexagonal, with no superlattice--reflecting the absence of a structural modulation in this phase. Previous resistivity studies at various levels of nonstoichiometry in Cu 2−x S showed that the phase transition is abrupt on heating and cooling only when the Cu vacancies (x) present are less than 1% of the atomic weight (15), thus confirming the stoichiometry of our nanoparticles. Since Cu vacancies are acceptors in Cu 2 S, the hole carrier (hereafter denominated as "e + ") concentration in our p-type nanoplates n e + is less than 1%.…”
Section: Resultssupporting
confidence: 56%
“…27 Liquid-like behavior of Cu ion in the p-type Cu 2−δ S (δ = 0-0.03) affects thermal properties. 28 With increasing temperature, the heat capacity at constant pressure C p decreased clearly at T > 400 K and fell below the Dulong-Petit value at T > 800 K, leading to the reduction in κ ∝ C p . The suppression in C p was due to the reduction in C v , the specific heat at constant volume.…”
Section: B Digenite and Chalcocite (P-type)mentioning
confidence: 99%
“…The increase in C p with T in excess of the Dulong-Petit value is in contrast with the suppression in C v (T) or C p (T) reported for superionic conductors Cu 2−δ S and Cu 2−δ Se. 28,29 Therefore, Cu ions in the colusites are not in a liquid-like state but in a localized state. Although the ZT values for the colusite are lower than that for Cu 2−δ S, higher usability of colusites for the TE applications is observed due to less migration of Cu ions.…”
Section: Colusite (P-type)mentioning
confidence: 99%
“…Current efforts to improve zT are focused on the optimization of power factor α 2 σ through controlled doping or electron band engineering,7, 8, 9, 10, 11 suppression in κ L by alloying or nanostructuring,1, 2, 5, 6 and development of new materials with intrinsically low κ L 12, 13, 14, 15. Heat‐carrying phonons cover a broad spectrum of frequency, and the κ L is a sum of contributions from phonons of different frequencies.…”
mentioning
confidence: 99%